Research status and development trend of blockchain in cellular mobile communication system - ·iping ZUO; Shi JIN; Shengli ZHANG (Dianxin kexue)
The blockchain is essentially a distributed database that can be safely updated without the need for third-party intermediaries.The blockchain technology is introduced into the 6G cellular mobile communication system to ensure the privacy of users,reduce the cost of resource allocation and communication services,and support different distributed applications.In order to realize the organic combination of mobile communication and blockchain technology,it is predicted to be one of the key technologies of 6G cellular mobile communication.From the blockchain combined with internet of things (IoT),edge computing,spectrum allocation,interference management,a detailed introduction was introduced,and the latest research progress of international academic circles in this direction was expounded in recent years,and on this basis,the development trend of blockchain technology in 6G cellular mobile communication was further prospected.